Contracts as rent-seeking devices: Evidence from German soccer - Eberhard Feess; Michael Gerfin; Gerd Muehlheusser (University of Bern, Department of Economics, 2010)
Recent theoretical research has identified many ways how contracts can be used as rent-seeking devices vis-à-vis third parties, but there is no empirical evidence on this issue so far. To test some basic qualitative properties of this literature, we develop a theoretical and empirical framework in the context of European professional soccer where (incumbent) teams and players sign binding contracts which are, however, frequently renegotiated when other teams (entrants) want to hire the player. Because they weaken entrants in renegotiations, long-term contracts are useful rent-seeking devices for the contracting parties. However, they also lead to allocative distortions in the form of deterring efficient transfers. Since incumbent teams tend to benefit more from long-term contracts in renegotiations than players do, these must be compensated ex ante by higher wages when agreeing to a long-term contract. Using data from the German Bundesliga, our model predictions are broadly confirmed.
Keywords: L14; J63; L40; L83; 330; strategic contracting; rent-seeking; empirical contract theory; long-term contracts; breach of contract; Arbeitsvertrag; Vertragstheorie; Rent-Seeking; Fußballsport; Professioneller Sport; Sportler; Lohnverhandlungen; Deutschland